Walsh, Daphne. New Perlican Photograph of two men and a child. - Barrett, Terra (1944)
A photograph of Uncle Frank Piercey (left), Ray (centre), and William Hobbs (right) in 1944-45 in New Perlican. Uncle Frank is wearing a navy uniform and William Hobbs is wearing a suit. Ray is in a small coat. Above the photo says "Family Memories" and below the photo says "Uncle Frank Ray & Dad" The photograph was printed by Kodak.